Multiple Grounds Only Partially Addressed: Canon 1677 - Rinere, Elissa (CLSA advisory opinions, 2001-2005, 2001)
Multiple grounds have been set in a marriage nullity case. The question to be addressed by the judges in the case is on one ground "and/or" the second ground. Can the judges opt not to address one of the grounds, while rendering an affirmative decision on the other ground? Or must the judges answer both grounds with either and affirmative or a negative judgment? If the judges leave one ground unaddressed, can the same ground be used in a future case? Or is the act of leaving one of the grounds unaddressed equal to a negative judgment?